Optimization of supporting college students entrepreneurship environment. Issue 2 (31st March 2020) - Miao, Yujun; Fan, Hongyun; Yuan, Bo
Abstract: With an increasing number of college students, improving the entrepreneurial ability of college students has become an important factor affecting economic development. A good business environment is a necessary prerequisite for the success of college students as entrepreneurs. At present, the research on the entrepreneurial environment available to college students is limited to literature review, with more theoretical research and less indexing systems for research. The main aim of this paper is to construct an index system of college students' entrepreneurial environment. The objective is to enable college students to quickly integrate into society and play positive roles in the government, school, and society. The conclusion is that optimizing the entrepreneurial environment of college students is the need of social stable development. By adopting reasonable methods, college students' entrepreneurial ability can be further improved, which is also to achieve social progress. It is necessary to optimize the entrepreneurial environment of college students, including expanding aid policies, supporting college students to start their own businesses, improving the social enterprise service system of college students, and strengthening the implementation of policies.